Green Advertising and It's Impact on Green Purchase Behavior among Gen-Z - Rizkynugraheny, Andien Dwi; Pakarti, Piji; Aryanto, Vincent Didiek Wiet; Fatmawati, Elia Resha (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Abstract This study aims to identify the effect of green advertising and environmental quality awareness on green purchase behavior through environmental attitude as an intervening variable on Milo gen-Z consumers in Semarang City. This research uses quantitative methods. Data collection used a questionnaire instrument distributed online and analysis using Partial Least Square Structural Equation Modeling (PLS-SEM). The result showed that green advertising has no effect on green purchase behavior. Environmental quality awareness and environmental attitude have a positive effect on green purchase behavior. Green advertising and environmental quality awareness have a positive effect on environmental attitude. Therefore, Milo is expected to deepen the green advertising message and prove that they really want to commit to the environment, not just a marketing strategy. Future researchers are expected to explore other generation and other related variables, such as influencer campaigns, and the level of customer satisfy action in sustainable products.